A pecuária bovina no assentamento rural de São José da Boa Morte (Cachoeiras de Macacu - RJ) - Paixão, Rita Leal (2009)
The present study aimed to investigate a rural region, deriving from agrarian reform (assentamento rural) in Cachoeiras de Macacu, RJ, namely São José da Boa Morte, in order to evaluate the livestock production established by the farmers. This study was performed in three different stages. In the first one information on many subjects concerning aspects such as health, income, the relationship with environment and living conditions was collected by using a standardized interview. At this first stage it was already noticed that pasture areas were expanding in the region. One year later, a second evaluation comprising 114 lots (second stage) confirmed that there was cattle growing in 58 % of them. In the third stage we interviewed the most important cattle breeders in order to know their livestock production and opinions. Results showed that cattle is crossbred and fated mainly to milk production with poor monetary investment by the farmers. Results also indicated that cattle is an advantageous economic alternative to the farmers. They were pleased with the outcome of their choice and expressed the wish of continuing living there, despite of recognized problems (lack of technical advice, precarious roads and others). These findings are important in order to understand which factors are involved in the permanence of the farmers in their land instead of moving to the surroundings of the big cities.